prove that cos11+sin11/cos11-sin11=tan56

 tan 56 = tan(45+11)

tan45 = tan11

  • -13

LHS= cos11+sin11/cos11-sin11

divide both numerator and denominator by cos11

= 1+tan11/1- 1tan11

since tan 45=1 now we wil subtitute this value of 1 here in numerator

=tan45+tan11/1-tan45tan11 (since it is the formula for tan (a+b)so)

=tan(45+11)

=tan56

  • 81
= 1+tan11/1- 1tan11

since tan 45=1 now we wil subtitute this value of 1 here in numerator

=tan45+tan11/1-tan45tan11 (since it is the formula for tan (a+b)so)

=tan(45+11)

=tan56
  • 4
how (cos11/cos11)-(sin11/cos11) = 1-1tan11
  • -1
My dear, find your answer LHS= cos11+sin11/cos11-sin11

divide both numerator and denominator by cos11

= 1+tan11/1- 1tan11

since tan 45=1 now we wil subtitute this value of 1 here in numerator

=tan45+tan11/1-tan45tan11 (since it is the formula for tan (a+b)so)

=tan(45+11)

=tan56
  • 0
What are you looking for?